Average replicated T-matrix approximation: valence band of non-crystalline metallic alloys - P.Yakibchuk; O.Volkov; S.Vakarchuk (Condensed Matter Physics, 2007)
Here we present a new approximation for calculation of density of states of multi-component metallic alloys using Lloyd formula. We consider the average square of T-matrix as the pair replication of scattering system. The analytical expressions are probed on TixMn1-x and AlxNi1-x binary alloys. The results are in good agreement with the predicted behavior of density of states for such systems.